Marketing Management of Islamic Financial Services in the Digital Era - Leni Riski Hayati; Ahmad Habibi; Muhammad Iqbal Fasa (International Publisher, 2025)
The research aims to analyze in depth the marketing management of Islamic financial services in the digital era, which is currently at a historical crossroads due to the acceleration of digital transformation and the Industrial Revolution 4.0. This study uses a qualitative approach with the method of Systematic Literature Review (SLR). The results of the analysis indicate that adaptation to the Sharia digital marketing mix (7PS), such as technology-based products and physical evidence that transform into digital evidence, must be integrated with strict Sharia compliance. Managerial success depends on Shariah-compliant innovation, strengthening cybersecurity, and Human Resource Investment with dual competencies, with the Sharia Banking-as-a-Service model proposed as a solution to address inequalities in the digital infrastructure of SMEs.